2013
DOI: 10.1186/1757-7241-21-36
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of video self-instruction in cardiopulmonary resuscitation for lay persons

Abstract: BackgroundCardiopulmonary resuscitation (CPR) improves outcomes after cardiac arrest. Much of the lay public is untrained in CPR skills. We evaluated the effectiveness of a compression-only CPR video self-instruction (VSI) with a personal manikin in the lay public.MethodsAdults without prior CPR training in the past year or responsibility to provide medical care were randomized into one of three groups: 1) Untrained before testing, 2) 10-minute VSI in compressions-only CPR (CPR Anytime, American Heart Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
(28 reference statements)
0
2
0
1
Order By: Relevance
“…This dataset (available in the accompanying Supplementary Excel Spreadsheet file) summarises, in 28 tables, the psychomotor skill data extracted from 31 primary peer-reviewed articles that met the inclusion criteria for the related systematic review [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]. The psychomotor skills for which data were extracted and reported were: compression rate, compression depth, duration of interruptions to compressions, chest recoil, hand placement, proportion of adequate or ’correct’ compressions, ventilation volume, compression-to-ventilation ratio, duty cycle and overall skills.…”
Section: Datamentioning
confidence: 99%
“…This dataset (available in the accompanying Supplementary Excel Spreadsheet file) summarises, in 28 tables, the psychomotor skill data extracted from 31 primary peer-reviewed articles that met the inclusion criteria for the related systematic review [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]. The psychomotor skills for which data were extracted and reported were: compression rate, compression depth, duration of interruptions to compressions, chest recoil, hand placement, proportion of adequate or ’correct’ compressions, ventilation volume, compression-to-ventilation ratio, duty cycle and overall skills.…”
Section: Datamentioning
confidence: 99%
“…Situational and social contexts are also important considerations. Studies have shown that rescuers’ gender, occupation, CPR training experience, and income level were associated with the public's attitudes toward performing CPR (Godfred et al, 2013; Shams et al., 2016). In addition, the public's attitudes of bystander CPR may be influenced by cultural or psychosocial variables, which require further investigation (Lu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Auch Online-Tutorials vor BLS-Trainings resultierten in signifikant besseren praktischen Maßnahmen der Teilnehmenden 145. Der Lerneffekt bei Video-basiertem CPR-Training ist umstritten und aktuell Gegenstand mehrerer Forschungen 144,[146][147][148][149]. Bei diesen Beispielen sind vor allem die gute Durchführbarkeit und die Ressourcen-Einsparung ein wesentlicher Vorteil.…”
unclassified